PENGARUH JUMLAH PENGULANGAN PENGUKURAN TERHADAP KETELITIAN DAN KEPRESISIAN MULTIMETER DIGITAL DALAM MENGUKUR TEGANGAN DAN ARUS PADA RESISTOR - Baddariah Khopipa Pulungan; Nezha Iriany; Khalisha Husna; Oktaria Magdalena; Zahra Arjeti; Habibi Azka Nasution; Winsyahputra Ritonga (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to evaluate the extent to which variations in the number of measurement repetitions, namely n=10, n=20, and n=30, affect the accuracy and precision of the PHYWE 07122-00 digital multimeter (3½-digit DMM) in measuring voltage and current across three resistors: R1 and R2 (390 kΩ) and R3 (10 kΩ). A quantitative experimental approach with a repeated measurement design was employed. Percentage error was used as an indicator of accuracy, while the coefficient of variation (CV) served as an indicator of precision. All data processing and visualization were carried out using the Python ecosystem, including NumPy, SciPy, Matplotlib, and Seaborn, producing heatmap-based visualizations. The findings reveal that voltage measurements yielded exceptionally high accuracy (% error < 0.10%) with stable precision (CV 0.33–0.54%) across all repetition levels. In contrast, current measurements on R1 and R2 showed lower accuracy, attributed to the extremely small current (~7.69 µA) approaching the noise floor of the DMM’s microampere range rather than the number of repetitions per se. Overall, increasing the number of measurement repetitions did not consistently improve accuracy or precision, and the initial hypothesis was not confirmed.